2015
DOI: 10.1155/2015/372819
|View full text |Cite
|
Sign up to set email alerts
|

Third-Degree Hindpaw Burn Injury Induced Apoptosis of Lumbar Spinal Cord Ventral Horn Motor Neurons and Sciatic Nerve and Muscle Atrophy in Rats

Abstract: Background. Severe burns result in hypercatabolic state and concomitant muscle atrophy that persists for several months, thereby limiting patient recovery. However, the effects of burns on the corresponding spinal dermatome remain unknown. This study aimed to investigate whether burns induce apoptosis of spinal cord ventral horn motor neurons (VHMNs) and consequently cause skeletal muscle wasting. Methods. Third-degree hindpaw burn injury with 1% total body surface area (TBSA) rats were euthanized 4 and 8 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…To identify whether spinal expressions of FNDC5/irisin were affected by burn injury, we introduced third-degree burn on the right hind paw of each rat [ 12 , 17 , 38 ]. The ipsilateral spinal cord of L4–L6 segments corresponding to innervation on the hind limb [ 39 ] and cerebrospinal fluid (CSF) were obtained at 4 weeks postburn.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify whether spinal expressions of FNDC5/irisin were affected by burn injury, we introduced third-degree burn on the right hind paw of each rat [ 12 , 17 , 38 ]. The ipsilateral spinal cord of L4–L6 segments corresponding to innervation on the hind limb [ 39 ] and cerebrospinal fluid (CSF) were obtained at 4 weeks postburn.…”
Section: Resultsmentioning
confidence: 99%
“…An experimental full-thickness burn model indicated a reduction of conduction velocities postburn [ 16 ]. Our previous study on a burn rat model also indicated increased apoptosis in the spinal cord ventral horn postburn, resulting in denervation muscle atrophy [ 17 ]. Ma et al further indicated that microglial activation in the ventral horn resulted in neuronal apoptosis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedures were approved and conduced in accordance with the guidance of the Institutional Animal Care and Use Committee at Kaohsiung Medical University (IACUC Approval Number: 106047). On day 0 (D0), all animals received either a third-degree burn or sham burn injury and wound care following a previous thermal model [68]. The rats were randomly allocated into four groups of six rats each: (1) a sham-control group (sham burn group) which received a sham burn and no drug treatment;…”
Section: Methodsmentioning
confidence: 99%
“…The right hind paw of each rat topped with 100-g weight (to maintain a standardized surface contact) was placed, plantar side down, on a temperaturecontrolled metal surface for 10 seconds [68]. The metal surface was set at 25 ± 0.5°C for the sham burn group.…”
Section: Methodsmentioning
confidence: 99%